Inventory and Characterization of Leaf and Rhizome Morphology of Zingiberaceae Family Plants in the Kediri Region - M. Fauzan Putra Rahmatullah; Sulistiono Sulistiono; Ida Rahmawati (Pro-Life, 2026)
The Zingiberaceae family is a group of monocot plants widely distributed in tropical regions with high morphological diversity. This study aimed to describe in detail the leaf and rhizome morphological characters of 12 Zingiberaceae species found in the Kediri region, East Java, namely C. zanthorrhiza, C. longa, C. zedoaria, C. caesia, C. soloensis, Z. officinale, Z. officinale var. amarum, Z. zerumbet, A. galanga, A. zerumbet, K. galanga, and B. rotunda. The study was conducted using a descriptive exploratory method with a snowball sampling technique. Characters observed included leaf length and width, leaf apex and base shape, leaf venation patterns, as well as rhizome color, texture, aroma, shape, and branching pattern. The results showed that all species share pinnate leaf venation and entire leaf margins as characteristic features of the Zingiberaceae family. Morphological variation was found primarily in leaf dimensions, rhizome flesh color, and rhizome aroma. Rhizomes of all species exhibited a sympodial branching pattern. Striking differences were found between genera, particularly in rhizome flesh color: Turmeric spp. are generally orange to purple, Zingiber spp. are creamy yellow, and Kaempferia galanga is white. This morphological data can serve as a reference for field identification, conservation efforts, and the development of biology teaching materials based on local biological potential.